Skrining Fitokimia dan Potensi AktivitaS Antioksidan Ekstrak Etanol Daun Hijau dan Daun Merah Kastuba - Baiq Sopiah; Handa Muliasari; Emmy Yuanita (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Free radicals are an atom or molecule that has unpaired electron in its outer orbital that causes maked this reactive and unstable molecule. Free radicals when exposed continuously in the body are believed to cause several diseases include atherosclorosis, ischemia, cancer and premature aging therefore, antioxidant compounds is needed to inhibit the formation of free radicals. Kastuba (Euphorbia Pulcherrima Willd.) is one of the plants that has the potential as a natural antioxidant. The aim of this study was determining the content of active chemical compounds and free radical inhibitory potential of kastuba leaves ethanol ekstract.The procedures of this study were material collection, plant determination, simplicia production, extraction, phytochemical screening and qualitative free radical inhibition test with TLC (Thin Layer Chromatography). Phytochemical screening aim to determine the chemical compounds component of kastuba leaves ethanol extract including flavonoids, tannins and terpenoid test. The potential of free radical inhibition was carried out qualitatively with the TLC, DPPH (1,1-diphenyl-2-picrylhydrazyl) spray reagent. The results showed that kastuba leaves ethanol extract for both green leaves and red leaves contained flavonoids, tannins and terpenoids, and both leaves had the potential as free radical inhibition that indicated by yellow spots on TLC after DPPH reaction spray.